Factors Influencing the Health Examination in Unmarried Women - Ju Young Ha; Ji Hyang Youn; Yeong Suk Lee; Hyun Jung Lee (Korean Society of Women Health Nursing, 2014)
PURPOSE: This study was to investigate factors that influence health examination for unmarried women. METHODS: A correlation study was carried out with 144 unmarried women with an age range of 35~49 years through self-administered questionnaires. This questionnaire included Health Belief Model modifying factors (demographic . sociological, structural, and cues to action variables). Data were analyzed using descriptive statistics, chi2-test, multiple logistic regression. RESULTS: The mean age of participants was 37.2+/-2.67 years. Rates for breast cancer, cervical cancer and comprehensive health examination were each 34.7%, 38.2% and 94%. In multiple logistic regression analysis, influencing factors on physical examination were age(OR=0.06, 95% CI: 0.02~0.26), personal medical insurance (OR=6.30, 95% CI: 1.60~24.82), housemate (OR=7.63, 95% CI: 2.58~22.52), exercise (OR=3.72, 95% CI: 1.37~10.12) in breast cancer examination, and age (OR=0.08, 95% CI: 0.02~0.34; OR=0.07, 95% CI: 0.01~0.85), personal medical insurance (OR=14.17, 95% CI: 2.94~68.23), sexual experiences (OR=3.38, 95% CI: 1.28~8.91), drinking (OR=2.92, 95% CI: 1.14~7.49) in cervical cancer examination. CONCLUSION: The results emphasize the necessity of preparing nursing education and intervention in consideration of associated factors which influence on the health examination in unmarried women.